Double Aortic Arch Mimics the Clinical Characteristics of Severe Reactive Airway Disease in a Pediatric Patient - Yesilbas, Osman; Kus, Hazar Dogus; Sik, Guntulu; Citak, Agop; Temur, Bahar; Yozgat, Can Yilmaz; Temur, Hafize Otcu; Cakir, Erkan; Yozgat, Yilmaz (GEORG THIEME VERLAG KG, 2020)
Reactive airway disease is a prevalent condition that can be detected in the early infancy period. The condition might also deteriorate into asthma in some cases. If infants do not respond to the treatment of persistent wheeze and coughing, other rare causes should be investigated. The complete form of vascular ring is an extremely uncommon congenital cardiovascular abnormality. Double aortic arch constitutes the most significant portion of the complete vascular ring anomalies. Clinical manifestations of the anomaly are mainly respiratory due to the tracheal compression and mimicking the conditions of asthma. There have not been many reports about the clinical presentations of double aortic arch being remarkably similar to the same clinical manifestations of asthma in the literature. As far as we can be sure, there have not been any reported cases about severe reactive airway disease that caused a patient to have a life-threatening condition in the pediatric intensive care unit. Herein, we present a 5-month-old girl who had double aortic arch. Her anatomical aberration was diagnosed by three-dimensional computed tomography angiography of thorax, and the anomaly mimicked the clinical characteristics of life-threatening severe reactive airway disease.
Keywords: double aortic arch; reactive airway disease; respiratory insufficiency; childhood